Higher premorbid serum testosterone predicts COVID-19-related mortality risk in men. Issue 1 (1st June 2022) - Yeap, Bu B; Marriott, Ross J; Manning, Laurens; Dwivedi, Girish; Hankey, Graeme J; Wu, Frederick C W; Nicholson, Jeremy K; Murray, Kevin
Abstract: Objective: Men are at greater risk from COVID-19 than women. Older, overweight men, and those with type 2 diabetes, have lower testosterone concentrations and poorer COVID-19-related outcomes. We analysed the associations of premorbid serum testosterone concentrations, not confounded by the effects of acute SARS-CoV-2 infection, with COVID-19-related mortality risk in men. Design: This study is a United Kingdom Biobank prospective cohort study of community-dwelling men aged 40–69 years. Methods: Serum total testosterone and sex hormone-binding globulin (SHBG) were measured at baseline (2006–2010). Free testosterone values were calculated (cFT). the incidence of SARS-CoV-2 infections and deaths related to COVID-19 were ascertained from 16 March 2020 to 31 January 2021 and modelled using time-stratified Cox regression. Results: In 159 964 men, there were 5558 SARS-CoV-2 infections and 438 COVID-19 deaths. Younger age, higher BMI, non-White ethnicity, lower educational attainment, and socioeconomic deprivation were associated with incidence of SARS-CoV-2 infections but total testosterone, SHBG, and cFT were not. Adjusting for potential confounders, higher total testosterone was associated with COVID-19-related mortality risk (overall trend P = 0.008; hazard ratios (95% CIs) quintile 1, Q1 vs Q5 (reference), 0.84 (0.65–1.12) Q2:Q5, 0.82 (0.63–1.10); Q3:Q5, 0.80 (0.66–1.00); Q4:Q5, 0.82 (0.75–0.93)). Higher SHBG was also associated with COVID-19 mortality risk ( P = 0.008), but cFT was not ( P = 0.248). Conclusions: Middle-aged to older men with the highest premorbid serum total testosterone and SHBG concentrations are at greater risk of COVID-19-related mortality. Men could be advised that having relatively high serum testosterone concentrations does not protect against future COVID-19-related mortality. Further investigation of causality and potential underlying mechanisms is warranted.